傾聽與理解學童的學習需求： 四所小學性教育螺旋式課程的行動研究 Attentiveness and Comprehension of Children's Learning Needs: Action Research Along with the Spiral Curriculum for Sexuality Education in Four Elementary Schools - 李雪菱 Shiue-Ling Lee (Higher Education Foundation, 2022)
為傾聽與理解學童的性教育學習需求，以發展適合小學生的性教育螺旋式課程，研究者跨越四所小學投入八年的行動研究。研究結果提出：青春期性教育提前從小一開始，由淺而深的螺旋式課程適切可行。內容包括不斷重複加深、加廣的實質內涵：性健康態度、生殖教育、法律、身體自主與界限、基本人權與尊重、身體意象的迷思、性別氣質、人我關係、媒體識讀、性別認同、性傾向認同、情感教育、性別平等教育與性別教養的反思與自處。對應十二年國民基本教育基本性別平等議題學習主題與實質內涵，小一起尚需加入原中學教育階段法律權益（J9），小三起即需融入身體意象迷思（J2）。教師應敏覺學童的生理發展與科技環境，更應視傾聽為性教育專業知能，並提升對學童的文化敏感度。 The study presented in this paper is an attempt to help attend to and comprehend the learning needs of school children during their sexuality education journey. Our eight-year action research had been conducted in four elementary schools in order to develop a spiral curriculum suitable for school pupils receiving puberty education. This research indicates that it is proper and viable for children to begin puberty programs from the very first grade in elementary school, alongside the courses of study with gradually spiraling complexity on sexuality education issues deep and broad. The substantial content of our courses concentrates mainly on the following: sexual health attitude, sex education, education on related laws, bodily integrity and body boundaries, the basic human rights and respect, the myth of ones body image, gender presentations, relationships with others, media literacy, gender identity, sexual identity, emotional education for personal relationships, reflection and self-management on gender equity education and gender cultivation. In this paper, we suggest that, in light of the gender equity learning framework for the present 12-year Basic Education Curriculum Guidelines, acquired knowledge of legal empowerment at the junior high education section (J9) be included in the course of the elementary first graders and higher, and the myth of the body image (J2) be incorporated into the course of the third and higher graders. It is also suggested that a teacher be made aware of childrens physical development as well as todays technological communications environment encompassing them, and his or her attentiveness to culture among children be a requisite for sexuality education expertise and skills.